2013
DOI: 10.1097/sle.0b013e31828e3954
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Floppy Nissen Fundoplication

Abstract: LFNF is an effective long-term treatment for gastroesophageal reflux disease, yielding similar results to open fundoplication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 33 publications
1
21
0
1
Order By: Relevance
“…The availability of laparoscopic antireflux surgery (LARS) has changed the threshold for referring patients to surgery. Several studies have reported excellent short- [ 4 ] and long-term [ 5 , 6 ] results for this procedure.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of laparoscopic antireflux surgery (LARS) has changed the threshold for referring patients to surgery. Several studies have reported excellent short- [ 4 ] and long-term [ 5 , 6 ] results for this procedure.…”
Section: Introductionmentioning
confidence: 99%
“…This technique has been described previously. [ 5 11 ] The patients who underwent surgery for a hiatal hernia (type I and type III) underwent a procedure that entailed dissection of the hernia sac, reduction of the hernial sac and its contents from the mediastinum into the abdominal cavity. The posterior hiatal repair was routinely performed.…”
Section: Methodsmentioning
confidence: 99%
“…The availability of laparoscopic antireflux surgery (LARS) has changed the threshold for referring patients to surgery. Several studies have reported excellent short-[ 4 ] and long-term[ 5 ] results for this procedure. Some studies have already shown that the benefits of a shorter hospital stay and reduced post-operative morbidity associated with laparoscopic techniques for anti-reflux surgery also apply to elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…ГПОД составляют 98 % всех грыж диафрагмы, а в 50 % случа-ев не вызывают никаких клинических проявлений и, следовательно, не диагностируются [3]. Несмотря на достижения в хирургии пищевода, этот раздел остает-ся одним из наиболее проблемных [4,5].…”
Section: Introductionunclassified